A Multi-Echelon Inventory System with Information Exchange - Moinzadeh, Kamran (Management Science, 2002)
In this paper, we consider a supply-chain model consisting of a single product, one supplier, and multiple retailers. Demand at the retailers is random, but stationary. Each retailer places her orders to the supplier according to the well-known (Q,R) policy. We assume that the supplier has online information about the demand, as well as inventory activities of the product at each retailer, and uses this information when making order/replenishment decisions. We first propose a replenishment policy for the supplier, which incorporates information about the inventory position of the retailers. Then, we provide an exact analysis of the operating measures of such systems. Assuming the inventory/replenishment decisions are made centrally for the system, we compare the performance of our model with those that do not use information in their decision making, namely, systems that use installation stock policies via a numerical experiment. Based on our numerical results, we identify the parameter settings under which information sharing is most beneficial.